Medium molecular weight polar substances of the cuticle as tools in the study of the taxonomy, systematics and chemical ecology of tropical hover wasps (hymenoptera: stenogastrinae) - Hashim, Rosli; Turillazzi, S.; Baracchi, D.; Dapporto, L.; Teseo, S. (2010)
The Stenogastrinae wasps have been proposed as a key group for an understanding of social evolution in insects, but the phylogeny of the group is still under discussion. The use of chemical characters, in particular cuticular hydrocarbons, for insect taxonomy is relatively recent and only a few studies have been conducted on the cuticular polar substances. In this work, we ascertain, by the matrix-assisted laser desorption ionization-time of flight mass spectrometry technique, that different species of primitively eusocial hover wasps have different compositions of the epicuticular polar compounds ranging from 900 to 3600 Da. General linear model analysis and discriminant analysis showed that the average spectral profiles of this fraction can be diagnostic for identification of the species. Moreover, for the first time we show population diversification in the medium MW polar cuticular mixtures in insects. In conclusion, the results demonstrate that the chemical characters are consistent with the physical characters and the study support the importance of medium MW polar substances as powerful tools for systematics (chemosystematics) and chemical ecology (fertility signal and population characterization) in a primitively social insect taxon.